ANALISIS PROFIL BERKAS RADIASI LINEAR ACCELERATOR 6MV PADA PENGGUNAAN VIRTUAL WEDGE DENGAN GAFCHROMIC FILM - Arisa Dwi Sakti; Eko Hidayanto; Heri Sutanto; Sanggam Ramantisan (Youngster Physics Journal, 2015)
Analysis of the radiation beam profile linear accelerator 6mV on the use of virtual wedge with gafchromic film done as a virtual wedge calibration on the linear accelerator . Virtual wedge calibration was originally done using ionization chamber detector, but its use is not efficient because for one-time calibration with an area of 10 x 10 cm2 field takes 10 times the exposure with the results of 10 data transform one dose profile curve . It takes a dosimeter that can capture the entire virtual dose results wedge with one exposure is gafchromic films with an area that can be customized . This research was conducted with a virtual wedge on the Siemens PRIMUS linear accelerator , scanner Epson Stylus 10000 XL , Solid Water Phantom , Matlab Program and Excel Program. This research begin to find the corelation between radiation beam and pixel value on gafchromic film with field size 1x 1 cm2. This corelation in used to find profile dose of virtual wedge from gafchromic film with field size 1 x 11 cm2. Variation fof gafchromic film is in this angle on 150, 300, and 450, opening jaws in Y1and Y2and teh last variation of half beam position in (-10 until 0),(-5 until 5) and (0 until 10). This research find that in higher beam dose, make the darkness film but lowerpixel value.ther are 2 corection in jaws position Y2 half beam (-10 until 0)300 and jaws position Y2 half beam (0 until1 0) 450. No one of ymetrisity value higher than 3% appropriate with AAPM TG-47.Keyword: virtual wedge, profil dosis, gafchromicf film, half beam